Implementation of oral procedures for non-penal matters in the Ecuadorian judicial system, and the treatment of it in the Code of General Procedures - Bermeo, José Elías (USFQ Law Review, 2013)
Ecuador has failed at trying to adopt an oral judicial procedure in non-penal matters for more than a decade. This article wants to analyze the current civil law procedure, its evolution, and the following projects: Unified Procedural Code of CEJA and Code of General Procedures presented by the Judiciary Council. Both projects analyze how oral procedures can reduce the waiting time of judicial resolutions. However, the article also treats the challenges of implementing oral procedures in Ecuador.
Keywords: Orality; Project of the General Procedures Code; Project of the Unified Procedural Code of CEJA; Challenges of the Oral System